Feasibility for the Use of a Standardized Fitness Testing Protocol Among Australian Fitness Industry Professionals. Issue 3 (3rd July 2018) - Bennie, Jason A.; Wiesner, Glen H.; Vergeer, Ineke; Kolbe-Alexander, Tracy L.; De Cocker, Katrien; Alexander, Chris; Biddle, Stuart J. H.
ABSTRACT: Purpose : There is currently no standardized testing protocol for assessing clients' fitness/health within the Australian fitness industry. This study examined the perceptions of the feasibility of using a standardized testing protocol among Australian fitness industry professionals.Method : In 2014, 1, 206 registered fitness industry professionals (aged 17–69 years) completed an online survey. Perceived feasibility for using a standardized testing protocol was assessed based on responses to 6 items. Respondents were classified as having a high level of perceived feasibility if they reported all 6 items to be " definitely feasible ." A multivariate logistic regression analysis, adjusting for demographic and fitness industry-related factors (e.g., qualification/years of experience), assessed the likelihood of having a high level of perceived feasibility.Results : Overall, 25.5% (95% CI [23.1%, 28.0%]) of the sample perceived the use of a standardized testing protocol as highly feasible. Items ranked most often as " definitely feasible " were " undertaking training to use the protocol " (55%) and " conducting follow-up testing every 6 to 12 weeks " (52%). After adjustment for the effect of confounding factors, casually employed professionals (OR = 0.63; 95% CI [0.45, 0.90]) and group instructors (OR = 0.58; 95% CI [0.41, 0.82]) were less likely to perceive standardized testing protocols as highly feasible.Conclusions : Among a large sample of Australian fitness industry professionals, slightly more than a quarter perceived using a standardized testing protocol to be highly feasible. Group instructors and casual employees perceived lower feasibility. Further research should determine the barriers to implementing a standardized testing protocol across the fitness industry.